Politeness Strategies In Donald Trump’s Government Shutdown Speech: A Pragmatic Analysis - Putri, Tiara Julia; Painah; Agus, Cecep (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
This study seeks to identify and describe how polite language strategies are used in government political speeches related to the issue of government shutdowns. The approach used is descriptive qualitative, using the pragmatic theoretical framework of Brown and Levinson (1987). The research data comes from recordings of official speeches posted on YouTube, where note-taking and listening techniques were used to collect information. The results of the research show that speakers tend to use Positive Politeness strategies to strengthen the sense of togetherness among party members, and use Direct Strategies on the Main Issue to convey urgent policy commands. The significance of these findings lies in the understanding of how language is used tactically to maintain social harmony while maintaining political dominance in difficult times. The core conclusion of this research is that the determination of politeness strategies is greatly influenced by the urgency of the situation and the power relationship between the speaker and the listener. Further studies could examine changes in politeness strategies in intercultural political debates or through various social media platforms to observe broader pragmatic movements.